Overcoming Old in Age-Friendliness - Lindenberg, J. (J Soc Work Pract, 2015)
In this article, we explore views on an age-friendly space in the Netherlands by analysing the responses of older individuals (N = 54) in focus groups and by examining the perspectives around an age-friendly zone in the Netherlands, Parkstad Limburg. We found that a central issue in the wishes for living at a later age are adjustments to envisioned physical limitations that come with the ageing process; this includes adjustments to ensure safety, accessibility and mobility, in order to facilitate older individuals' efforts to stay engaged with the world around them. In their wishes, the older participants constructed ideal dwelling places that closely resembled a senior home, but at the same time they rejected wishing to live in a place that was identified as a senior home. We explain this paradox by the representation of such a space as being for old people, i.e. needy older individuals, which was not how the older participants wished to be identified. We conclude that the conception of age-friendly environments will have to face the difficult challenge of overcoming the association with old age, while simultaneously taking into account adjustments that signify and relate to the ageing process and that seem inescapably tied to oldness.